The young prince - Smith, Ronald L. (Ronald Lenard), 1959- (Marvel, 2018)
T'Challa is training to inherit Wakanda, a technologically-advanced African kingdom ruled by his father, when he is unexpectedly sent to a Chicago public school with his best friend where he encounters an ancient evil that he must destroy.